PENGARUH CITRA MEREK, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA WARUNG NASI GORENG PELANGI DI SITUBONDO - Balqis Raudhatul Jannah; Siti Soeliha; Rini Kartika Sari (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The increasingly intense competition in the culinary industry requires business owners to maintain customer loyalty. This study aims to examine the extent to which brand image, product quality, and service quality influence customer loyalty, both directly and indirectly through customer satisfaction as an intervening variable, at Warung Nasi Goreng Pelangi in Situbondo. A quantitative research method was employed, involving 94 respondents selected from a total population of 1,580 customers. Data were collected through questionnaires and analyzed using Smart PLS 3.0. The findings reveal that both brand image and product quality have a significant and positive effect on customer satisfaction. Additionally, service quality shows a significant and positive effect on customer loyalty. However, service quality does not have a significant effect on customer satisfaction. Furthermore, brand image, product quality, and customer satisfaction do not have significant effect on customer loyalty, either directly or indirectly through customer satisfaction as an intervening variable.